2017
DOI: 10.1111/apa.13991
|View full text |Cite
|
Sign up to set email alerts
|

Children born extremely preterm had different sleeping habits at 11 years of age and more childhood sleep problems than term‐born children

Abstract: EPT children had different sleep habits to term-born controls at 11 years of age, including those with no NDD. The prevalence of sleep problems increased with increasing NDD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 28 publications
4
29
0
1
Order By: Relevance
“…In 11‐year‐old children born very preterm (<28 weeks completed GA, or weighing <1000 g), who had neurodevelopmental disabilities (assessed at 5 years of age), there was a higher percentage of sleep problems compared to term‐matched control counterparts (Stangenes et al . ). The preterm‐born infants went to bed earlier, had longer sleep‐onset latency, increased night waking, and they slept longer.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In 11‐year‐old children born very preterm (<28 weeks completed GA, or weighing <1000 g), who had neurodevelopmental disabilities (assessed at 5 years of age), there was a higher percentage of sleep problems compared to term‐matched control counterparts (Stangenes et al . ). The preterm‐born infants went to bed earlier, had longer sleep‐onset latency, increased night waking, and they slept longer.…”
Section: Introductionmentioning
confidence: 97%
“…Notably, however, preterm infants with no reported neurodevelopmental disabilities also had sleep difficulties, which were similar to those reported for their preterm counterparts with neurodevelopmental disabilities (Stangenes et al . ). Longer nocturnal sleep duration, more night awakenings, and longer daytime sleep duration was also observed in 6‐month‐old infants born at an older age (31.5 ± 3.2 weeks GA, 1467 ± 588.6 g, mean±SD) compared to term control infants (Huang et al .…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, for an α = 0.05 and 1-β = 0.8, even our weakest main comparison between the early preterm group (n = 83) and controls (n = 341) in the actigraphy analysis would be able to detect or exclude a mean difference of 0.34 SD. This is charitable considering that the mean effect size in studies that investigate preterm circadian preference (Asaka & Takada 2010;Björkqvist et al 2014;Hibbs et al 2014;Maurer et al 2016;Natale et al 2005;Stangenes et al 2017;Strang-Karlsson et al 2008;Strang-Karlsson et al 2010), and in adult VLBW studies in general, tend to be around the order of magnitude of~0.5 (Hovi et al 2007;Pyhälä et al 2011). The few formally statistically significant differences showed no consistent pattern and are likely to have arisen by chance, or are possibly related to issues not studied here.…”
Section: Discussionmentioning
confidence: 99%
“…Also, among 13-year-old preterms (<37 weeks), a larger proportion were "morning types" compared to controls when assessed with the Junior MEQ and Junior Composite Scale (Natale et al 2005). A Norwegian questionnaire study (Stangenes et al 2017) of extremely preterm (<28 weeks or ELBW) 11-year-olds displayed 0.4h earlier bedtime, but correspondingly longer time in bed. Most participants of the aforementioned studies are characterized by a very low birth weight and/or very short gestational age.…”
Section: Introductionmentioning
confidence: 92%
“…We have previously shown that children born extremely preterm (EPT) have more sleep problems throughout childhood than children born at term, and that the prevalence increases with the degree of neurodevelopmental disability 10. Children born EPT are also at increased risk of behavioural problems and respiratory morbidities,11 12 but we do not know how such difficulties affect their sleep.…”
Section: Introductionmentioning
confidence: 99%